ANALISIS JASA LINGKUNGAN PENYEDIA AIR DI KECAMATAN TOBELO KABUPATEN HALMAHERA UTARA - Philipus Kastanya; Dellen N. Matulessy (Program Studi Manajemen Hutan, Pascasarjana Universitas Pattimura, 2023)
Environmental Services are the benefits of ecosystems and the environment for humans and the sustainability of life which includes providing natural resources, managing nature and the environment, supporting natural processes, and preserving cultural values. One of the important environmental services classified as service providers in Tobelo District is water supply ecosystem services. The purpose of this study is principally to analyze land cover, natural vegetation and ecoregions (landscapes) in the Tobelo District, as well as to analyze the water supply ecosystem services in the Tobelo District. The method used in this study is the visual classification method through the ArcGIS application for processing and analysis of land cover, natural vegetation and ecoregions (landscapes). Meanwhile, the spatial join method using ArcGIS aims to produce spatial information on water supply ecosystem services in Tobelo District. The results of the analysis show that areas have ecosystem services are classified as very high in providing water in Tobelo District covering an area of ​​4,492.23 Ha or 36.71% with an IJE of 3.16-4.40, located in primary dry forest land cover, which is a natural vegetation of Lowland Monsoon Forest and Lower Monsoon Mountain Forest, with a landscape (ecoregion) belonging to the Structural Hills of the Halmahera Complex and the Volcanic Mountains of the Gamalama Complex. In addition, very high category of ecosystem services is also found in dryland agriculture, with the Gamalama Complex Volcanic Plain landscape. Meanwhile, the ability of ecosystem services in the widest Tobelo Subdistrict area to provide water in the area, is included in the medium category.